(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study assessed the financial-related factors that influence the adoption of computerizedaccounting system (CAS) for improved performance of small and medium scale enterprises (SMEs) in Anambra State. Two research questions and two null hypotheses guided the study. The studyadopted survey research design, and 5,396 (3,137 managers and 2,259 accounting officers) of SMEs in Anambra State were used as the population of the study. The sample was 361 managers andaccounting officers of SMEs. Structured and validated questionnaire containing 10 items on a five- point Likert scale was used for data collection. The reliability of the instrument was established usingCronbach Alpha formula which yielded apha values of .88 and .78. Mean and t-test were usedtoanalyze the data. Findings of the study showed that managers and accounting officers agreed that fundaccessibility and fund management factors influenced the adoption of CAS for improved performance. It was also found that the mean ratings of managers and accounting officers do not differ regardinginfluence of fund accessibility and fund management factors on the adoption of CAS for improvedperformance of SMEs. Based on the findings of the study, the researchers conclude that fundaccessibility and fund management factors influence the adoption of CAS for improved performanceof SMEs. It was recommended among others that; government and financial institutions in Nigeriashould ensure that loans and credit facilities provided to SMEs are easily accessible